2013
DOI: 10.3390/catal3010219
|View full text |Cite
|
Sign up to set email alerts
|

Photocatalytic Oxidation Processes for Toluene Oxidation over TiO2 Catalysts

Abstract: Gas-solid heterogeneous photooxidation of toluene over TiO 2 catalyst was studied to investigate the factors controlling the catalytic activities. The toluene photooxidation behavior on TiO 2 was strongly affected by the formation and oxidation behavior of intermediate compounds on TiO 2 , and their accumulation decreased the reaction rate for toluene photooxidation. The formation and oxidation behavior of the byproduct compounds depended on the initial concentration of toluene and water vapor. In situ Fourier… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(16 citation statements)
references
References 37 publications
0
16
0
Order By: Relevance
“…(Debono et al 2011a;Einaga et al 2013;Farhanian and Haghighat 2014;Gunschera et al 2009;Sleiman et al 2009;Zhang et al 2011). The occurrence of the compounds could either be explained by pollutant or matrix degradation.…”
Section: By-productsmentioning
confidence: 98%
“…(Debono et al 2011a;Einaga et al 2013;Farhanian and Haghighat 2014;Gunschera et al 2009;Sleiman et al 2009;Zhang et al 2011). The occurrence of the compounds could either be explained by pollutant or matrix degradation.…”
Section: By-productsmentioning
confidence: 98%
“…However, if PCO are conducted at room temperature, the active sites on the photocatalyst’s surface could be gradually occupied by irreversibly chemisorbed intermediates, which retard the reactions. For example, during the photocatalytic oxidation processes for toluene over TiO 2 catalysts, it was found that the toluene photooxidation behavior was strongly affected by the formation and oxidation behavior of intermediate compounds [90]. The study carried out by Nakajima et al , showed that H 2 SO 4 treatment of TiO 2 surface provides higher photocatalytic removal efficiency on toluene which can be ascribed to the fast decomposition of intermediates by surface strong acid itself [91].…”
Section: Removal Of Indoor Vocs and Formaldehyde Via Photocatalytimentioning
confidence: 99%
“…AOPs are based on in situ generation of reactive radical species, mainly OH ‚ , by means of solar, chemical or other forms of energy [12,13]. In this field the photocatalytic oxidation (PCO) in the presence of TiO 2 to give total or partial oxidation of liquid or gaseous contaminants to benign substances is one of the most promising environmentally friendly techniques for the abatement of volatile organic compounds (VOCs) [14,15]. In fact, the formation of electron-hole pairs on TiO 2 by light irradiation with a suitable light source plays a key role in the mineralization of VOCs into CO 2 and H 2 O.…”
Section: Introductionmentioning
confidence: 99%